Perivascular epithelioid cell tumour (PEComa): an unusual cause of painful defaecation. Issue 2 (9th February 2022) - Chua, Deborah; Loh, Alwin Hwai-Liang; Tan, Emile; Seow-En, Isaac
Abstract : Perivascular epithelioid cell tumours (PEComa) are rare tumours of mesenchymal origin. We report a 39-year-old patient who presented with painful defecation secondary to an anorectal mass. The diagnosis of anorectal PEComa was confirmed following excision and histopathological examination. We review the literature and discuss the management of this uncommon entity.